Teacher Interpersonal Communication in Motivating Student Learning at Muhammadiyah 2 Sidoarjo Elementary School during the Covid-19 Pandemic - Cindy Permata Sari; Kukuh Sinduwiatmo (Journal of Islamic and Muhammadiyah Studies, 2023)
This study aims to formulate problems regarding teacher interpersonal communication in motivating student learning along with what are supporting and inhibiting factors of teacher-student interpersonal communication during the covid-19 pandemic. The research method used is qualitative with data collection techniques through observation, interviews, and documentation. With the techniques of determining the informant using purposive sampling technique. The result showed that the teacher’s role was crucial in interpersonal communication in order to motivate student learning during covid-19 pandemic. Meanwhile, the inhibiting factors of interpersonal communication between student and teacher were found in the form of technical, physical, semantic, psychological, and social environment factors. The supporting factors themselves are proximity to communication targets, supportive attitude, empathy, teacher self-image, to a positive learning environment.